The role of leaf cutting and fire on extrafloral nectaries and nectar production in Stryphnodendron adstringens (Fabaceae, Mimosoideae) plants. Issue 4 (5th May 2022) - Delgado, Marina Neves; de Morais, Helena Castanheira; Rossatto, Davi Rodrigo
Abstract: Herbivory pressure is an important ecological aspect to determine quantitative variation in plant defenses, such as the number of extrafloral nectaries (EFNs) and their nectar amount and quality. Extrafloral nectaries can attract ants, which can be considered a type of induced plant defense. Besides, plants tend to invest more in defense when they are more vulnerable to herbivores. Therefore, we aimed to elucidate if Stryphnodendron adstringens (Fabaceae), a common Cerrado tree species, when subjected to damage (by manual leaf cutting and experimental fire) would produce a greater number of EFNs and changes its nectar quality on newly produced leaves in comparison with plants not subjected to these treatments. Leaf damage was performed artificially directly on the plant branches and at the entire plant canopy (by means of scissors or fire events). Extrafloral nectary density was higher in new leaves produced after the treatment application (artificial herbivory and fire) in comparison with plants under control treatment. The amount of nectar was also higher under treatments in comparison with control, with a significant change on nectar quality in plants subjected to the treatments of artificial herbivory. The results provided support for the hypothesis that EFNs are an inducible defensive strategy in S. adstringens, confirming the existence of phenotypic plasticity given environmental pressures. Abstract :